Lifetime prevalence of dysgraphia and associated family environment characteristics in primary schools - Abed, Sameeha Naser; Abbas, Dhakam Mohammed; Dawood, Israa (Intelektual Pustaka Media Utama, 2023)
The current study was designed to screen and observe dysgraphia in primary schools in Wassit governorate in Iraq. In addition, to identify the presence of any family environment characteristics associated with dysgraphia, a cross-sectional study has been applied during the period from 1st November 2018 to the end of March 2019, which was conducted on 421 students from public and private primary schools which were randomly selected. The lifetime prevalence of students with dysgraphia was 27% in the present study. Most students (53.2%) were equal to or less than 10 years old. In the population sample, dysgraphia prevailed more in boys than girls. Illiteracy was higher for the students who have fathers with dysgraphia (39.3%) as compared to the students who have non- dysgraphia fathers (29.4%). The difference was more significant for the age, gender, and level of education of parents (p<0.05). It was concluded that dysgraphia among primary school students aged 7-12 years occurs at a lifetime prevalence of nearly one-third of them. In our study, it was affirmed that dysgraphia is a problem that most commonly affects males more than females. It is important to note that the difference between the two groups was statistically significant in regard to age, gender, and level of education of parents.